Sistematic Literatur Review (SLR) : TINJAUAN REGULASI GLOBAL TERHADAP BAKU MUTU GETARAN AKIBAT AKTIVITAS TRANSPORTASI DI INDONESIA - Handayani, Dewi; Mahmudah, Amirotul M. H.; Triharningsih, Septia Nur (Jurnal Teknik Sipil dan Arsitektur, 2025)
Transportation modes, whether land, sea, or air, can cause significant vibration impacts that can disturb the surrounding environment. The vibrations caused by the three modes of transportation are ground vibrations that impact people in the environment around the transportation mode. Vibration impacts from these modes of transportation must be controlled through strict regulations for human comfort and health and to maintain the integrity of building structures around the operating area. Indonesia has regulations regarding vibration quality standards regulated in KepMenLH No. 49 of 1996 concerning vibration levels due to facilities and infrastructure for human activities. Various countries also have updated regulations for transportation vibration levels such as Japan, Germany, Australia, and others. The latest transportation vibration quality standard regulations are more comprehensive, making it possible to control vibration impacts more effectively. This research aims to review the regulation of vibration quality standards in Indonesia due to transportation activities with global regulations at both national and international levels. Through comparative descriptive analysis, this research will identify shortcomings in Indonesian regulations and provide recommendations for improvement. The result of this research is that Indonesia's regulations require updating to ensure that the standards used remain relevant and effective in facing future vibration challenges. However, as the majority of countries in the world still use the vibration parameters used in KepMenLH No. 49, these parameters are still sufficient.